Drivers of young adults’ voluntary compliance with COVID-19 protective measures: results from a multi-method study - Anne Reinhardt; Winja Weber; Constanze Rossmann (BMC Public Health, 2022)
Abstract Background With the easing of governmental COVID-19 restrictions, promoting voluntary public compliance with protective measures becomes essential for the pandemic evolution. A highly relevant target group for such health promotion are adolescents and young adults since they showed a strong decline in compliance throughout the pandemic. Building on an extended version of the Theory of Planned Behavior, this article investigates drivers of young people’s intentions to engage in voluntary COVID-19 measures in phases of re-opening. Methods We conducted a sequential multi-method study among 14- to 29-year-olds in Germany: (1) a semi-standardized online survey (N = 88) to examine underlying beliefs and (2) a standardized online survey (N = 979) to identify influencing factors of compliance. The pre-study addressed the respondents’ perceptions about wearing a mask, social distancing, and avoiding crowded locations (open-ended questions). Responses for all protective measures were aggregated to identify general behavioral, normative, and control beliefs about COVID-19 protective measures. In order to gain generalizable insights into the factors determining voluntary compliance intentions in younger adults, we conceptualized the model constructs in the subsequent standardized online survey as formative measures based on their underlying beliefs. PLS-SEM was used to examine the effects of attitudes, subjective norms, perceived behavioral control, risk perceptions, and knowledge on young people’s intentions to comply (main study). Furthermore, a multi-group analysis was conducted to investigate differences between compliers and non-compliers. Results The pre-study revealed that young people’s instrumental attitudes not only cover reasons of protection but also aspects of self-presentation (e.g., being a role model). The main study showed that besides knowledge and perceived severity of illness, instrumental attitude is the strongest predictor of intention to comply. The influence is even stronger in the group of non-compliers. Conclusion This article highlights the importance of theory-based campaign planning and provides practical guidance to health communicators on how to increase voluntary compliance with COVID-19 protective measures in adolescents and young adults. The findings demonstrate the great potential of combining the Theory of Planned Behavior with risk perception and knowledge to gain deeper insights into the feelings and thoughts of younger target groups during a health crisis.